KONTRIBUSI TENAGA KERJA PEREMPUAN TERHADAP PENDAPATAN KELUARGA PADA UD MANDIRI DESA PANGU KECAMATAN RATAHAN TIMUR - Sifora Susan Agouw; Tommy F. Lolowang; Vicky R. B. Moniaga (AGRI-SOSIOEKONOMI, 2018)
This study aims to see how much does working women’s contribution to family income. The research located in Pangu Village, East Ratahan Sub-district. This research was conducted in April until June 2017. The research used primary and secondary data. Primary data were collected by direct interview technique on 6 (Six) respondents. They are Women Workers who work in UD MANDIRI as dodol and sugar palm wrapper. Secondary data used written data inthe form of documents in the Village Office obtained from the village head. Primary data were analyzed used descriptive analysis and presented in tabular form. The results showed that the average income of women worker amounted to Rp.500.000, - in 1 (one) month. The contribution of female labor to family income was 28% in 1 (one) month.*eprm*.